"What If You Die?": Skipped‐Generation Caregivers' Reported Conversations With Their Grandchildren About Death. Issue 2 (25th February 2021) - Freeman, Jessica D.; Elton, Jessica
Abstract : Objective: This study focused on grandparent caregivers' communication about death with their grandchildren. Background: Skipped‐generation grandfamilies have become more common in the United States. However, much research on death communication focuses on traditional parent–child(ren) nuclear families, making it necessary to understand how families with other structures, such as skipped‐generation grandfamilies, address this topic. Method: This qualitative study applied communication privacy management as a guiding theory and used progressive focusing to collect 30 in‐depth interviews with grandparent caregivers. Interviews were analyzed using thematic analysis. Results: Three themes and eight subthemes emerged. The first theme centered on grandparent caregivers' motivations for disclosing about death to grandchildren and comprised three subthemes: Exposure to Death and Lifecycle Concepts, Grandchild Curiosity, and Unique Grandparent Caregiver Concerns. The second theme reflected grandparent caregivers' motivations to conceal information about death, which included Age Inappropriateness, Trauma Aversion, and Lack of Utility. The third theme captured grandparent caregivers' perceptions of whether their grandchildren were concerned about caregiver death. Conclusion: Like traditional parent–child(ren) nuclear families, grandfamilies identify death as an important but challenging topic to discuss. However, the unique characteristics of grandfamilies magnify challenges and complexities of discussing death. Implications: The findings contribute to communication specialists', social workers', and psychologists' understanding of how grandfamilies manage privacy surrounding death.